Development of Germ Plasm Cultivation in National Park Buffer Zone - Rinekso Soemadi (Media Konservasi, 1990)
The objectives of the germ plasm cultivation in the buffer zone are :(1) to increase people participation in the conservation or the national park potentials(2) to motivate people cultivate some species of the national park germ plasm for their conservation.The choice of species to be planted should be based on the following criteria :(a) its usefulness and economic value for the local people, (b) easy to cultivate with simpletechnology, and (c) frequently used by the local people.The location of the land to be planted should be close to or bordering the settlement area, and on that land there is already a forest plantation or a marginal forest which is designated as a buffer zone. The people who will be given the planting rights consist of : (a) those who have frequentlygathered forest products from the national park, (b) those who live close to or at the border of the national park, (c) those who have agricultural background, and (d) those who have strong motivation to implement the planned program. if this social forestry approach succeeded, the post-harvest technology and the marketing of the products should also be taken care of.